A diagnostic protocol designed for determining allergic causes in patients with blood eosinophilia - Jean-François Magnaval; Guy Laurent; Noémie Gaudré; Judith Fillaux; Antoine Berry (Military Medical Research, 2017)
Abstract Background Blood eosinophilia is a common laboratory abnormality, and its characterization frequently represents a quandary for primary care physicians. Consequently, in France, specialists and particularly hematologists, often must investigate patients who present with blood eosinophilia that often, but not always, occurs because of allergic causes. Both the Departments of Hematology and Parasitology at Toulouse University Hospitals established a collaboration to rule out allergic causes of eosinophilia, particularly helminthiases, prior to initiating more sophisticated investigations. Methods Since 2004, the authors employed the same protocol to investigate eosinophilic outpatients who attended the clinic of Parasitology at Toulouse University Hospitals, and they reported the performance of this diagnostic procedure that was designed to be rapid (no hospitalization required) and only moderately expensive. Results A total of 406 patients who presented with blood eosinophilia greater than 0.5 (×109, giga cells per litter, G/L) had an allergic etiology in 350 (86.2%) cases. Among the remaining 56 subjects, 17 did not undergo a follow-up and 39 were referred to another specialized department, mostly Hematology. However, only 21 patients attended then were subsequently investigated. Non-allergic causes of eosinophilia, including 3 cases of the lymphoid variant of hypereosinophilic syndrome and 2 cases of myeloproliferative disorder, were identified in 14 patients, whereas 7 remained diagnosed as having idiopathic eosinophilia. Conclusion This study underlines the need to investigate patients presenting with even moderate blood eosinophilia. The work-up that was employed appears to be efficient and versatile and may be used by any medical specialist, such as in hematology, infectious disease, or internal medicine departments, who needs to investigate eosinophilic patients and should initially rule out any etiology of allergic eosinophilia.